Incidence and pattern of congenital heart disease in children: an observational cross-sectional study - Ullah, Mohammad Ata; Mamun, Sumaiya; Saha, Heemel; Al-Miraj, A. K. (International Journal of Research in Medical Sciences, 2025)
Background: The objective of this study was to analyse the incidence, pattern, and clinical presentation of congenital heart disease in children and evaluate associated risk factors. Methods: This observational cross-sectional study included 100 children aged 0-14 years diagnosed with CHD at department of cardiac surgery, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh duration of study was 1 year starting from January to December 2022. Detailed clinical evaluation, echocardiography, and relevant investigations were performed for all cases. Associated anomalies and maternal risk factors were documented. Results: Of 100 cases, 56% were males and 44% females (ratio 1.27:1). The majority (68%) were diagnosed in the first year of life. Acyanotic CHD predominated (72%) with ventricular septal defect being the most common lesion (30%), followed by atrial septal defect (15%) and patent ductus arteriosus (12%). Among cyanotic CHD (28%), tetralogy of Fallot was most frequent (15%). Common presenting features included breathing difficulty (45%), failure to thrive (38%), and recurrent respiratory infections (35%). Associated anomalies were present in 22% cases, with Down syndrome (8%) being the most common genetic association. Significant maternal risk factors included advanced age (15%) and diabetes mellitus (8%). Conclusions: The study demonstrated patterns of CHD consistent with global literature while highlighting regional variations. Early detection was achieved in the majority of cases, though late presentation remains a concern. The findings emphasize the need for comprehensive screening programs and improved healthcare access, particularly in resource-limited settings. Understanding these patterns can guide resource allocation and healthcare planning for better management of pediatric cardiac care.